2014
DOI: 10.1016/j.virol.2014.07.054
|View full text |Cite
|
Sign up to set email alerts
|

The agnoprotein of polyomavirus JC is released by infected cells: Evidence for Its cellular uptake by uninfected neighboring cells

Abstract: Poliomavirus JC replicates in glial cells in the brain, and causes the fatal demyelinating disease, progressive multifocal leukoencephalopathy (PML). PML is usually seen in patients with underlying immunocompromised conditions, notably among AIDS patients and those on chronic immunosuppressive regimens. The late leader sequence of JC virus contains an open reading frame encoding a small regulatory protein called agnoprotein. Agnoprotein contributes to progressive viral infection by playing significant roles in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
19
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 26 publications
4
19
0
Order By: Relevance
“…Similar change in CD spectra is reported for fibril forming peptides such as insulin (Zako et al 2009) and Aβ peptide (Tomaselli et al 2006). Recently, Agno was reported to exist outside of the infected cell (Otlu et al 2014). It is interesting to assume that the released Agno may form oligomers or aggregates with other β-sheet forming proteins such as myelin sheath (Kursula 2008) or amyloid beta fibrils (Giovanna et al 2010), resulting in various brain diseases.…”
Section: Discussionsupporting
confidence: 64%
“…Similar change in CD spectra is reported for fibril forming peptides such as insulin (Zako et al 2009) and Aβ peptide (Tomaselli et al 2006). Recently, Agno was reported to exist outside of the infected cell (Otlu et al 2014). It is interesting to assume that the released Agno may form oligomers or aggregates with other β-sheet forming proteins such as myelin sheath (Kursula 2008) or amyloid beta fibrils (Giovanna et al 2010), resulting in various brain diseases.…”
Section: Discussionsupporting
confidence: 64%
“…Recently, it was found that the JCV late regulatory protein, agnoprotein, is able to be released from JCV‐infected cells . Because agnoprotein is only expressed by cells that are actively replicating the virus and is released into the extracellular matrix, it is possible that detection of agnoprotein in clinical samples could serve as a biomarker for JCV reactivation.…”
Section: Tests Involving Minimally Invasive Assaysmentioning
confidence: 99%
“…The precise mechanism of this phenomenon is currently unknown. However, recent findings by Otlu et al (2014) demonstrate that agnoprotein is readily released from the infected cells. Further analysis of these three Phe mutants in release assays by our laboratory demonstrate that each may play a significant role in this process, because high proportion of each Phe-mutant agnoprotein appears to be trapped in cells during the release process.…”
Section: Peculiar Behavior Of Leu29 and Phe Mutants Of Agnoproteinmentioning
confidence: 98%
“…Two recent publications also argue against the membrane integration activity agnoprotein. In one of the reports, it was demonstrated that agnoprotein is released from infected and transfected cells into the culture medium (Otlu et al, ) suggesting that if agnoprotein is an integral component of the cell membrane, it is highly unlikely that it will be readily secreted into the cell culture medium unless one of the various forms of agnoprotein (monomeric, dimeric or oligomeric (Saribas et al, ) are favorably suitable for this process. In a second report, Johannessen et al () demonstrated that BKV agnoprotein interacts with α‐soluble N‐ethylmaleimide‐sensitive fusion attachment protein (α‐SNAP) (Johannessen et al, ), which is a ubiquitous and indispensable component of the membrane fusion machinery and is a part of a special membrane system such as Golgi apparatus, suggesting that agnoprotein may interact with cell surface molecules rather than inserting itself into the cell membranes.…”
Section: Role Of Agnoprotein In Viral Life Cyclementioning
confidence: 99%